Analysis of the effect of temporal and spatial baseline of radar images on the amount of coherence for detecting large-scale displacement gradients using interferometric synthetic aperture radar (Case study: Gol Gohar Sirjan Mine) (In Persian) - Siavash Shami (21362891) (2025)
Geomatics and GIT 97